Positive electrode active material and method for producing positive electrode active material

By using oxide precursors and performing specific heat treatment during the preparation process, the problems of low yield of positive electrode active materials, poor stability and high residual lithium are solved, and the life and capacity performance of secondary batteries are improved.

CN119920895APending Publication Date: 2025-05-02ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411499640.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-30
Filing Date
2024-10-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the preparation process, the existing positive electrode active substances have problems such as low yield, poor stability and high residual lithium, resulting in poor service life and capacity performance of the secondary battery.

Method used

By using oxide precursors and applying specific process methods during the preparation process, including the first and second heat treatments, controlling the full width of the crystal plane half-maximum and the lattice constant in the XRD pattern, a positive electrode active material with increased stability and reduced residual lithium was prepared.

Benefits of technology

The production of positive electrode active substances is increased, stability is improved and residual lithium is effectively removed, thereby improving the life and capacity performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102237320000161
    Figure BDA0005102237320000161
  • Figure BDA0005102237320000171
    Figure BDA0005102237320000171
  • Figure BDA0005102237320000172
    Figure BDA0005102237320000172
Patent Text Reader

Abstract

A positive electrode active material according to one embodiment of the present invention is a lithium composite oxide, and according to X-ray diffraction (XRD) analysis results using CuK [alpha] rays, the following relational expression (1) can be satisfied in an XRD pattern obtained by Rietveld fitting: 0.110 < = FWHM (104) < = 0.170, and the positive electrode active material is characterized in that: the X-ray diffraction (X-ray diffraction) analysis results of the X-ray diffraction (X-ray diffraction) analysis results of the X-ray diffraction (X-ray diffraction) analysis results of the X-ray diffraction (X-ray diffraction) analysis results of the X-ray diffraction (X-ray diffraction). A method of preparing a positive electrode active material according to an embodiment of the present invention may include preparing a first lithium composite oxide by performing a first heat treatment on a first mixture including the prepared oxide precursor, a lithium-containing compound, and a first cobalt-containing compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a method for preparing the same, and more particularly, to a positive electrode active material for a secondary battery prepared from an oxide precursor and a method for preparing the same. Background Art

[0002] With the development of portable mobile electronic devices such as smart phones, MP3 players, and tablet computers, the demand for secondary batteries capable of storing electric energy has increased explosively. In particular, with the emergence of electric vehicles, large and medium-sized energy storage systems, and portable devices that require high energy density, the demand for lithium secondary batteries is continuously increasing.

[0003] As a lithium composite oxide included in the positive electrode active material, a recently spotlighted material is lithium nickel manganese cobalt oxide Li(Ni x Co y Mn z )O2 (in this case, x, y, and z are atomic fractions of respective independent oxide constituent elements, 0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, and 0 < x + y + z ≤ 1). Compared with the positive electrode active material LiCoO2 that has been actively studied and used in the past, since this positive electrode active material is used at a high voltage, it has the advantage of high output capacity, and since the Co content is relatively low, it has the advantage of low price.

[0004] However, with the insertion and extraction of lithium ions during charge and discharge, such a lithium composite oxide is accompanied by volume changes. During charge and discharge, there are problems such as a sharp volume change in the primary particles of the lithium composite oxide, or the generation of cracks in the secondary particles with repeated charge and discharge, or the collapse of the crystal structure or the phase change of the crystal structure.

[0005] In order to compensate for this drawback, as a positive electrode active material for a secondary battery, the demand for a nickel (Ni)-rich system - high nickel type positive electrode active material in which the content of nickel (Ni) is 60 mol% or more relative to the total content of metals other than lithium (Li) has started to increase, and an increase in production volume is required.

[0006] However, the high nickel type positive electrode active material has a problem of reduced stability and shortened life due to the high Ni content. Also, due to the high Li / M ratio during the preparation process, the content of residual lithium after firing is high, so gelation occurs during the preparation of the electrode slurry, making it difficult to prepare a battery. Therefore, a cleaning process is introduced to remove the residual lithium, but there is a problem that the battery characteristics are reduced due to damage to the positive electrode surface during the cleaning process. Summary of the Invention

[0007] Technical Problem

[0008] The existing positive electrode active material is prepared by heat treating a hydroxide precursor together with a lithium-containing compound, but this has limitations in improving productivity. Therefore, the present invention aims to increase the yield by more than 10% by applying an oxide precursor when preparing the positive electrode active material, and it is necessary to develop a technology for applying it.

[0009] The present inventors aim to control the full width at half maximum (FWHM (deg., 2θ) of the (104) crystal plane and / or the full width at half maximum (FWHM) of the (003) crystal plane in the XRD pattern obtained by Rietveld fitting based on the results of X-ray diffraction (XRD) analysis using CuKα rays, so as to improve battery performance such as life and capacity when applied to secondary batteries.

[0010] Furthermore, the inventors intend to prepare a positive electrode active material with increased stability and reduced residual lithium by applying a specific process method in the steps of performing a first heat treatment and / or a second heat treatment on an oxide precursor and a lithium-containing compound, thereby improving battery performance such as life and capacity when the positive electrode active material is applied to a secondary battery.

[0011] Technical Solution

[0012] The positive electrode active material according to one embodiment of the present invention includes a lithium composite oxide. According to the results of X-ray diffraction analysis using CuKα rays, the following relational expression 1 can be satisfied in an XRD pattern obtained by Rietveld fitting.

[0013] Relationship 1: 0.110 ≤ FWHM (104) ≤0.170,

[0014] In the above equation 1, the above FWHM (104) It refers to the full width at half maximum (FWHM (deg., 2θ)) of the (104) crystal plane at the XRD peak defined by the hexagonal lattice with the R-3m space group.

[0015] As one embodiment, according to the results of X-ray diffraction analysis using CuKα rays, the positive electrode active material may satisfy the following relational expression 2 in an XRD pattern obtained by Rietveld fitting.

[0016] Relationship 2: 0.080 ≤ FWHM (003) ≤0.130,

[0017] In the above equation 2, the above FWHM (003)It refers to the full width at half maximum of the (003) crystal plane at the XRD peak defined by the hexagonal lattice with the R-3m space group.

[0018] As one embodiment, the a-axis lattice constant of the positive electrode active material may be 2.860 to 2.890.

[0019] As one embodiment, the c-axis lattice constant of the positive electrode active material may be 14.190 to 14.200.

[0020] As one embodiment, the positive electrode active material may be in a bimodal form including first positive electrode active material particles having an average particle size (D50) of 8 μm or more and second positive electrode active material particles having an average particle size (D50) of 7 μm or less.

[0021] The method for preparing a positive active material according to an embodiment of the present invention comprises the following steps: preparing an oxide precursor; and preparing a first lithium composite oxide by first heat treating a first mixture including the prepared oxide precursor, a lithium-containing compound and a first cobalt-containing compound.

[0022] As an embodiment, after the step of preparing the first lithium composite oxide, the method further includes preparing a second lithium composite oxide by performing a second heat treatment on a second mixture including the prepared first lithium composite oxide and a second cobalt-containing compound.

[0023] As one embodiment, when in the step of preparing the above-mentioned first lithium composite oxide, the molar percentage of cobalt contained in the above-mentioned first cobalt-containing compound relative to the total amount of metal in the prepared above-mentioned oxide precursor is set to A, and in the step of preparing the above-mentioned second lithium composite oxide, the molar percentage of cobalt contained in the above-mentioned second cobalt-containing compound relative to the total amount of metal other than lithium in the prepared above-mentioned first lithium composite oxide is set to B, it can be 0.1≤A / B≤0.5.

[0024] As one embodiment, the first cobalt-containing compound may be Co3O4.

[0025] As one embodiment, the second cobalt-containing compound may be Co3O4.

[0026] As an embodiment, the second heat treatment temperature Y can be 690°C. <Y<720℃。

[0027] The positive electrode active material according to one embodiment of the present invention can be prepared by the above-mentioned method for preparing the positive electrode active material.

[0028] The positive electrode according to one embodiment of the present invention may include the positive electrode active material described above.

[0029] A secondary battery according to one embodiment of the present invention may include the above-mentioned positive electrode active material.

[0030] Effects of the Invention

[0031] One effect of the present invention is to prepare a positive electrode active material with increased production volume, increased stability and reduced residual lithium, so that when it is applied to a secondary battery, battery performance such as life and capacity can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The results show the effect of reducing nickel vacancy after the first heat treatment and the effect of removing residual lithium after the second heat treatment according to the preparation method of the embodiment of the present invention.

[0033] Figure 2 The graph shows a comparison of the (104) displacement changes after the first heat treatment and the second heat treatment according to the preparation method of the embodiment of the present invention based on the X-ray diffraction analysis results using CuKα rays. DETAILED DESCRIPTION

[0034] Expressions such as "comprising" and the like used in this specification should be understood as open-ended terms implying the possibility of including other structures.

[0035] The terms "preferred" and "preferably" used in this specification refer to embodiments of the present invention that can provide specified advantages under specified circumstances. However, other embodiments are not intended to be excluded from the scope of the present invention.

[0036] Furthermore, unless otherwise indicated in the context, singular forms used in the specification and the appended claims may be intended to include plural forms as well.

[0037] On the other hand, the technical features described below relate to an embodiment for achieving the desired effects of the present invention.

[0038] That is, the positive electrode active material and the method for preparing the positive electrode active material according to one embodiment of the present invention include the technical features of the following one embodiment, so that when applied to a secondary battery, the battery characteristics can be significantly improved.

[0039] The present invention relates to a positive electrode active material for a secondary battery and a method for preparing the positive electrode active material. The type of the secondary battery of the present invention is not limited, as long as it is a battery that can convert external electrical energy into chemical energy and store it for reuse. As a more preferred embodiment, the present invention may relate to a positive electrode active material for a lithium ion secondary battery and a method for preparing the positive electrode active material.

[0040] First, a positive electrode active material according to one embodiment of the present invention will be described.

[0041] The positive electrode active material according to one embodiment of the present invention may include a lithium composite oxide.

[0042] As one embodiment, the positive electrode active material may include nickel.

[0043] As one embodiment, the positive electrode active material may further include one or more selected from cobalt (Co), aluminum (Al), and manganese (Mn).

[0044] As one embodiment, the positive electrode active material may be represented by the following Chemical Formula 1.

[0045] Chemical formula 1:

[0046] Li a Ni x Co y M 1-x-y O2

[0047] In the above Chemical Formula 1, M is selected from the group consisting of Zr, Mn, Al, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.9≤a≤1.2, 0.5≤x≤1.0, 0.0≤y≤0.4, and 0.0≤1-xy≤0.4.

[0048] As one embodiment, the positive electrode active material may be represented by the following Chemical Formula 1-1.

[0049] Chemical formula 1-1:

[0050] Li a’ Ni x’ Co y’ M1 z’ M2 1-x’-y’-z’ O2

[0051] In the above chemical formula 1-1, M1 is Al or Mn, M2 is selected from the group consisting of Zr, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.9≤a'≤1.2, 0.5≤x'≤1.0, 0.0≤y'≤0.4, 0.0≤z'≤0.4, 0.0≤1-x'-y'-z'≤0.4.

[0052] As one embodiment, in the above Chemical Formula 1 and / or Chemical Formula 1-1, a and / or a' representing the molar percentage of lithium (Li) relative to the total molar percentage of metals other than lithium (Li) may be greater than 0.9, greater than 1.0, less than 1.2, less than 1.1, or less than 1.05.

[0053] As one embodiment, in the above Chemical Formula 1 and / or Chemical Formula 1-1, x and / or x' representing the molar percentage of nickel relative to the total molar percentage of metals other than lithium (Li) may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, it may be a high nickel oxide in which x and / or x' is 0.8 or more or 0.9 or more.

[0054] As one embodiment, in the above Chemical Formula 1 and / or Chemical Formula 1-1, y and / or y' representing the molar percentage of cobalt relative to the total molar percentage of metals other than lithium (Li) may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.

[0055] As one embodiment, the positive electrode active material may have a crystal structure of hexagonal α-NaFeO 2 (R-3m space group).

[0056] As one embodiment, according to the results of X-ray diffraction analysis using CuKα rays, the positive electrode active material may satisfy the following Relationship 1 in an XRD pattern obtained by Rietveld fitting.

[0057] Relationship 1: 0.110 ≤ FWHM (104) ≤0.170

[0058] In the above equation 1, the above FWHM (104) It refers to the full width at half maximum of the (104) crystal plane at the XRD peak defined by the hexagonal lattice with the R-3m space group.

[0059] As one embodiment, the FWHM (104) It may be 0.110 or more, 0.120 or more, 0.130 or more, 0.170 or less, 0.160 or less, 0.150 or less, or 0.140 or less.

[0060] In the present invention, during the XRD analysis process, the full width at half maximum (FWHM) value may deteriorate or error depending on various variables such as the conditions of the analysis equipment, the X-ray source, and the measurement conditions. Therefore, correction is performed using the full width at half maximum (FWHM) of a corundum disc used as a standard sample.

[0061] In the present invention, the corundum grinding disc used is a NIST corundum grinding disc.

[0062] In the present invention, X-ray diffraction analysis is performed by using Cu Kα radiation. The measurement was performed using a Bruker D8 Advance diffractometer at a step size (° / step) of 0.02° / step and a measurement time of 0.1 s / step.

[0063] As one embodiment, according to the results of X-ray diffraction analysis using CuKα rays, the positive electrode active material may satisfy the following relational expression 2 in an XRD pattern obtained by Rietveld fitting.

[0064] Relationship 2: 0.080 ≤ FWHM (003) ≤0.130

[0065] In the above equation 2, the above FWHM (003) It refers to the half maximum width of the (003) crystal plane at the XRD peak defined by the hexagonal lattice with the R-3m space group.

[0066] As one embodiment, the FWHM (003) It may be 0.080 or more, 0.090 or more, 0.100 or more, 0.130 or less, 0.120 or less, or 0.110 or less.

[0067] In one embodiment, the a-axis lattice constant of the positive electrode active material may be 2.860 or more, 2.870 or more, 2.871 or more, 2.872 or more, 2.873 or more, 2.890 or less, 2.880 or less, 2.875 or less, or 2.874 or less.

[0068] As one embodiment, the c-axis lattice constant of the positive electrode active material may be 14.185 or more, 14.190 or more, 14.192 or more, 14.193 or more, 14.200 or less, 14.195 or less, or 14.194 or less.

[0069] In the present invention, the a-axis lattice constant and the c-axis lattice constant are values ​​calculated by indexing XRD measurement data through Rietveld refinement.

[0070] As one embodiment, the positive electrode active material may include a plurality of positive electrode active material particles.

[0071] As one embodiment, the positive electrode active material particles may be secondary particles formed by agglomeration of one or more primary particles.

[0072] As one embodiment, the primary particles may include one or more crystallites.

[0073] As one embodiment, the secondary particles may be in the form of multiple particles or polycrystalline particles including two or more primary particles.

[0074] As one embodiment, the positive electrode active material may be in a unimodal form including positive electrode active material particles having an average particle size (D50) of 1 μm to 30 μm.

[0075] In the present invention, the average particle diameter (D50) is a particle diameter at 50% of the area cumulative distribution of particle diameters, and it can be measured by a laser diffraction method.

[0076] As another more preferred embodiment, the positive electrode active material may be in a bimodal form comprising first positive electrode active material particles having an average particle size (D50) of 8 μm or more and second positive electrode active material particles having an average particle size (D50) of 7 μm or less.

[0077] As one embodiment, in the case where the positive electrode active material is in a bimodal form, when the weight of the first positive electrode active material particles contained in the positive electrode active material is set to w1, and the weight of the second positive electrode active material particles contained in the positive electrode active material is set to w2, w1 / w2 can be 1.5 to 9.0 or 2.0 to 4.0. The invention can increase the energy density by using small particles existing in the pores between large particles in the bimodal positive electrode active material having such a mixing ratio, and can solve the problem of reduced battery characteristics caused by changes in the average particle size deviation between large particles and small particles.

[0078] As one embodiment, when the positive electrode active material of the present invention is in a bimodal form, the first positive electrode active material particles as large particles may be secondary particles formed by agglomeration of primary particles.

[0079] As one embodiment, the primary particles of the first positive electrode active material particles as large particles may include one or more crystallites.

[0080] As one embodiment, the secondary particles of the first positive electrode active material particles as large particles may be in the form of multiple particles or polycrystalline particles including a plurality of primary particles.

[0081] As one embodiment, the second positive electrode active material particles as small particles may be in the form of a single particle including one primary particle, and may be in the form of a single crystal when the primary particle consists of one crystallite.

[0082] As another embodiment, the second positive electrode active material particles as small particles may be in the form of multiple particles or polycrystalline particles including two or more primary particles.

[0083] Furthermore, when preparing the above-mentioned positive electrode active material, the cobalt added in the first heat treatment and / or the second heat treatment of the preparation method of the following positive electrode active material, in addition to being present in the lattice structure of the primary particles of the above-mentioned positive electrode active material, can also exist in the form of cobalt oxide on the surface of the secondary particles of the positive electrode active material and / or in the grain boundaries between the primary particles. The above-mentioned cobalt oxide can be an oxide of lithium combined with cobalt or an oxide of cobalt.

[0084] As one embodiment, the cobalt oxide may include a concentration gradient portion in which the molar concentration of cobalt changes. As an example, when the cobalt oxide includes lithium, the molar concentration of lithium may change. Also, as an example, the molar concentration of cobalt may change.

[0085] As one embodiment, the lattice structure of the primary particles of the positive electrode active material may contain an element added in addition to the above-mentioned cobalt. As an example, it can be one or more selected from aluminum (Al), titanium (Ti), zirconium (Zr), magnesium (Mg), zinc (Zn), boron (B), molybdenum (Mo), iron (Fe), nickel (Ni), barium (Ba) and tungsten (W).

[0086] On the other hand, in this specification, "element" is interpreted as including both a zero-valent state and an ion state.

[0087] As a further embodiment, the positive electrode active material may also form a coating oxide of other elements on the surface of the secondary particles and / or in the grain boundaries between the primary particles.

[0088] As one embodiment, the coating oxide may be represented by the following Chemical Formula 2.

[0089] Chemical formula 2:

[0090] Li p M3 q O r

[0091] In the above chemical formula 2, M3 is one or more selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd and Nd, and 0≤p≤10,0 <q≤8,2≤r≤13。

[0092] As an example, in the above chemical formula 2, M3 refers to a coating element, and the above coating oxide may be an oxide in which lithium and an element represented by M3 are combined, or an oxide of M3.

[0093] As an example, the coating oxide may be Li p Co q O r , Li p W q O r , Li p Zr q O r , Li p Ti q O r , Li p Ni q O r , Li p Al q O r , Li p Mo q O r 、Co q O r 、Al q O r , W q O r 、Zr q O r 、Ti q O r , B q O r , Li p (W / Ti) q O r , Li p (W / Zr) q O r , Li p (W / Ti / Zr) q O r , Li p (W / Ti / B) q O r , but not limited to this.

[0094] As one embodiment, when preparing the above-mentioned positive electrode active material, it can be a coating oxide, which contains elements that can be contained in the first mixture and / or the second mixture related to the preparation method of the positive electrode active material described below, and can be a coating oxide containing elements selected from aluminum, titanium, zirconium, magnesium, zinc, boron, molybdenum, iron, nickel, barium and tungsten.

[0095] On the other hand, the technical characteristics of the positive electrode active material may be related to the average technical characteristics of a plurality of positive electrode active material particles contained in the positive electrode active material.

[0096] On the other hand, the meaning of “≤”, “above” or “below” described in the present invention can be replaced by the meaning of “<”, “greater than” or “less than”.

[0097] Next, a method for preparing a positive electrode active material according to an embodiment of the present invention will be described.

[0098] First, as a method for preparing a positive electrode active material according to an embodiment of the present invention, a step of preparing an oxide precursor may be performed.

[0099] The positive electrode active material according to one embodiment of the present invention may be prepared from an oxide precursor.

[0100] As one embodiment, the oxide precursor may include nickel (Ni).

[0101] As one embodiment, the oxide precursor may further include one or more selected from cobalt (Co), aluminum (Al), and manganese (Mn).

[0102] As one embodiment, the oxide precursor may be represented by the following chemical formula 3.

[0103] Chemical formula 3:

[0104] Ni x Co y M 1-x-y O2

[0105] In the above Chemical Formula 3, M is selected from the group consisting of Zr, Mn, Al, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.5≤x≤1.0, 0.0≤y≤0.4, and 0.0≤1-xy≤0.4.

[0106] As one embodiment, the oxide precursor may be represented by the following chemical formula 3-1.

[0107] Chemical formula 3-1:

[0108] Ni x’ Co y’ M1 z’ M2 1-x’-y’-z’ O2

[0109] In the above chemical formula 3-1, M1 is Al or Mn, M2 is selected from the group consisting of Zr, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr and combinations thereof, and 0.5≤x'≤1.0, 0.0≤y'≤0.4, 0.0≤z'≤0.4, 0.0≤1-x'-y'-z'≤0.4.

[0110] As one embodiment, in the above Chemical Formula 3 and / or Chemical Formula 3-1, x and / or x' representing the molar percentage of nickel relative to the total molar percentage of metals may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, it may be a high nickel oxide in which x and / or x' is 0.8 or more or 0.9 or more.

[0111] As one embodiment, in the above Chemical Formula 3 and / or Chemical Formula 3-1, y and / or y' representing the molar percentage of cobalt relative to the total molar percentage of metals may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.

[0112] On the other hand, the above oxide precursor can be prepared by oxidizing a hydroxide precursor.

[0113] More specifically, the oxide precursor may be prepared by oxidizing a hydroxide precursor through heat treatment. In this case, the heat treatment temperature may be 300°C to 500°C, or 350°C to 450°C.

[0114] Next, a step of preparing a first lithium composite oxide by first heat-treating a first mixture including the prepared oxide precursor, the lithium-containing compound, and the first cobalt-containing compound may be performed.

[0115] As a more preferred embodiment, the first cobalt-containing compound may be Co3O4. Co3O4 can not only improve battery performance such as life and capacity, but also effectively remove residual lithium by reacting with residual lithium on the surface of particles.

[0116] As a further embodiment, the first mixture may further include a compound containing one or more elements selected from aluminum, titanium, zirconium, magnesium, zinc, boron, molybdenum, iron, nickel, barium and tungsten. More preferably, the first mixture may further include aluminum.

[0117] As one embodiment, the first heat treatment temperature may be 690° C. or higher, 700° C. or higher, 720° C. or lower, or 710° C. or lower.

[0118] In the method for preparing a positive electrode active material according to an embodiment of the present invention, after the step of preparing the first lithium composite oxide, no washing process may be performed.

[0119] In the preparation of positive electrode active materials, especially high nickel positive electrode active materials, the content of residual lithium after sintering is high due to the high Li / M ratio during the preparation process, so gelation occurs during the preparation of electrode slurry, making it difficult to prepare batteries. Therefore, a cleaning process such as adding particles to distilled water is introduced to remove residual lithium, but there is a problem of reduced battery characteristics due to damage to the positive electrode surface during the cleaning process.

[0120] The present invention can effectively remove residual lithium and reduce damage to the positive electrode surface by adding cobalt-containing compounds such as Co3O4 during the first heat treatment and / or the second heat treatment of the oxide precursor without the need for a cleaning process for removing residual lithium.

[0121] Furthermore, the present invention can effectively remove residual lithium and reduce damage to the positive electrode surface by optimizing the optimal cobalt addition content ratio and / or the second heat treatment temperature conditions in each heat treatment step without performing a cleaning process for removing residual lithium.

[0122] As one embodiment, after the step of preparing the first lithium composite oxide, a step of preparing a second lithium composite oxide by second heat treatment of a second mixture including the prepared first lithium composite oxide and a second cobalt-containing compound may be performed.

[0123] As a more preferred embodiment, the second cobalt-containing compound may be Co3O4. Co3O4 can not only improve battery performance such as life and capacity, but also effectively remove residual lithium by reacting with residual lithium on the surface of particles.

[0124] As a further embodiment, the second mixture may further include a compound containing one or more elements selected from aluminum, titanium, zirconium, magnesium, zinc, boron, molybdenum, iron, nickel, barium and tungsten. More preferably, the second mixture may further include titanium and zirconium.

[0125] On the other hand, in the present invention, in the step of preparing the first lithium composite oxide, the molar percentage of cobalt contained in the first cobalt-containing compound relative to the total amount of metals in the prepared oxide precursor is defined as A.

[0126] Furthermore, in the step of preparing the second lithium composite oxide, B is a molar percentage of cobalt contained in the second cobalt-containing compound relative to a total amount of metals other than lithium in the prepared first lithium composite oxide.

[0127] In this case, A / B may be 0.1 or more, 0.2 or more, 0.3 or more, 0.5 or less, or 0.4 or less.

[0128] The present inventors have newly recognized that the effects of cobalt added in the step of first heat-treating the oxide precursor and in the step of second heat-treating the oxide precursor are different.

[0129] More specifically, it was confirmed that the doping effect in the finally prepared positive electrode active material was maintained according to the cobalt content added during the first heat treatment, but the doping effect according to the cobalt content added during the second heat treatment was not significant.

[0130] On the contrary, it was confirmed that the residual lithium in the positive electrode active material decreased with the increase of the cobalt content during the first heat treatment and the second heat treatment of the oxide precursor, but even if the total cobalt content added was the same, the cobalt content added during the second heat treatment had a greater effect on the reduction of residual lithium ( Figure 1 ).

[0131] Therefore, considering the different effects of the cobalt added in the first heat treatment and the second heat treatment, the present inventors have recognized the need to optimize the ratio of the cobalt content added in each step.

[0132] Therefore, it was confirmed that even if the total cobalt content added is the same, when the cobalt content added in the first lithium composite oxide preparation step is 0.1 to 0.5 of the cobalt content added in the second lithium composite oxide preparation step, the doping effect and the synergistic effect of removing residual lithium can be maximized, while further improving the battery performance.

[0133] As one embodiment, A related to the cobalt content added in the above-mentioned first lithium composite oxide preparation step can be greater than 0.5 mol percent, greater than 0.8 mol percent, less than 3.5 mol percent, less than 3.0 mol percent, less than 2.5 mol percent, less than 2.0 mol percent, less than 1.5 mol percent or less than 1.2 mol percent.

[0134] As one embodiment, B related to the cobalt content added in the preparation of the second lithium composite oxide can be greater than 0.5 mol%, greater than 1.0 mol%, greater than 1.5 mol%, greater than 2.0 mol%, greater than 2.5 mol%, less than 4.0 mol% or less than 3.5 mol%.

[0135] As one embodiment, A+B (the molar percentage of cobalt added relative to the total amount of metals other than lithium) related to the total cobalt content added in the above-mentioned positive electrode active material preparation step can be greater than 2.5 molar percent, greater than 3.0 molar percent, less than 4.5 molar percent or less than 4.0 molar percent.

[0136] As a more preferred embodiment, the second heat treatment temperature Y may be 690°C or higher, greater than 690°C, 700°C or higher, 720°C or lower, less than 720°C or 710°C or lower.

[0137] The inventors optimized the content of cobalt added in the first heat treatment and the second heat treatment, and optimized the temperature of the second heat treatment for the optimized cobalt content.

[0138] As a result, it was confirmed that when the second heat treatment temperature Y was within the above range, the battery performance was further improved.

[0139] The positive electrode active material according to one embodiment of the present invention can be prepared by the above-mentioned method for preparing a positive electrode active material.

[0140] The above-mentioned positive electrode active material may include the technical features of the above-mentioned positive electrode active material.

[0141] The positive electrode according to one embodiment of the present invention may include the positive electrode active material described above.

[0142] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can have a known structure and be prepared according to a known preparation method. The binder, conductive material and solvent are not particularly limited as long as they can be used for the positive electrode collector of the secondary battery.

[0143] A secondary battery according to one embodiment of the present invention may include the above-mentioned positive electrode active material.

[0144] The secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but there is no particular limitation as long as the secondary battery can be used.

[0145] Hereinafter, embodiments of the present invention will be described in more detail.

[0146] Preparation of positive electrode active material

[0147] Example 1

[0148] (a) Preparation of hydroxide precursor

[0149] NaOH and NH4OH were added to a reactor to mix NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O in a molar ratio of 95:4:1 and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was added to the reactor to perform a hydroxide precursor synthesis reaction. After the reaction was completed, it was washed and dehydrated to obtain a composition of Ni 0.95 Co 0.04 Mn 0.01The large hydroxide particle precursor of (OH)2 was prepared by the same method with a molar ratio of 94:5:1.

[0150] (b) Preparation of oxide precursors

[0151] The hydroxide precursor prepared in the above step (a) was oxidized in a sintering furnace in an O2 atmosphere at a temperature of 400°C for 6 hours to obtain an oxide precursor.

[0152] The obtained average particle size (D50) of the above-mentioned large oxide particle precursor was 15.0 μm, and the average particle size (D50) of the small oxide particle precursor was 3.0 μm.

[0153] (C) Preparation of the First Lithium Composite Oxide

[0154] The first mixture is prepared by mixing the oxide large particle precursor and the oxide small particle precursor prepared in the above step (b) in a weight ratio of 7:3, LiOH as a lithium-containing substance (Li / metal molar ratio = 1.015), Co3O4 weighed with a Co content of 0.925 molar percent relative to the total amount of the metal of the above oxide precursor, and Al(OH)3 weighed with an Al content of 0.85 molar percent. Then, the sintering furnace in the O2 atmosphere is heated to 705°C for 2 hours and 20 minutes, and the above mixture is subjected to the first heat treatment for 8 hours, and then furnace cooling and disintegration are performed to obtain the first lithium composite oxide.

[0155] (d) Preparation of the Second Lithium Composite Oxide

[0156] The second mixture is prepared by mixing the first lithium composite oxide prepared in the above step (c) and Co3O4 weighed with a Co content of 2.775 mole percent, TiO2 weighed with a Ti content of 0.2 mole percent, and ZrO2 weighed with a Zr content of 0.1 mole percent relative to the total amount of metals other than lithium in the above first lithium composite oxide. Then, the sintering furnace in the air atmosphere is heated to 705°C for 2 hours and 20 minutes, and the above mixture is subjected to a second heat treatment for 8 hours, and then furnace cooling is performed to prepare the second lithium composite oxide.

[0157] Example 2

[0158] A second lithium composite oxide was prepared in the same manner as in Example 1, except that the calcination furnace was heated to 690° C. to perform the second heat treatment in the step (d).

[0159] Example 3

[0160] A second lithium composite oxide was prepared in the same manner as in Example 1, except that the calcination furnace was heated to 720° C. to perform the second heat treatment in the step (d).

[0161] Example 4

[0162] The second lithium composite oxide is prepared in the same manner as in Example 1 above, except that Co3O4 weighed with a Co content of 1.85 mol percent is mixed in the above step (c), Co3O4 weighed with a Co content of 1.85 mol percent is mixed in the above step (d), and the sintering furnace is heated to 690°C for a second heat treatment.

[0163] Example 5

[0164] The second lithium composite oxide was prepared in the same manner as in Example 1, except that Co3O4 weighed to have a Co content of 1.85 mol% was mixed in step (c), and Co3O4 weighed to have a Co content of 1.85 mol% was mixed in step (d).

[0165] Example 6

[0166] The second lithium composite oxide is prepared in the same manner as in Example 1 above, except that Co3O4 weighed with a Co content of 1.85 mol percent is mixed in the above step (c), Co3O4 weighed with a Co content of 1.85 mol percent is mixed in the above step (d), and the sintering furnace is heated to 720°C for a second heat treatment.

[0167] Example 7

[0168] The second lithium composite oxide is prepared in the same manner as in Example 1 above, except that Co3O4 weighed to have a Co content of 2.775 mol percent is mixed in the above step (c), Co3O4 weighed to have a Co content of 0.925 mol percent is mixed in the above step (d), and the sintering furnace is heated to 690°C for a second heat treatment.

[0169] Example 8

[0170] The second lithium composite oxide was prepared in the same manner as in Example 1, except that Co3O4 weighed to have a Co content of 2.775 mol% was mixed in step (c), and Co3O4 weighed to have a Co content of 0.925 mol% was mixed in step (d).

[0171] Example 9

[0172] The second lithium composite oxide is prepared in the same manner as in Example 1 above, except that Co3O4 weighed to have a Co content of 2.775 mol percent is mixed in the above step (c), Co3O4 weighed to have a Co content of 0.925 mol percent is mixed in the above step (d), and the sintering furnace is heated to 720°C for a second heat treatment.

[0173] Preparation of lithium secondary batteries

[0174] The positive electrode slurry was prepared by dispersing 95.5 weight percent of the positive electrode active material prepared according to the above embodiment, 2.5 weight percent of artificial graphite, and 2 weight percent of polyvinylidene fluoride (PVDF) binder into 2.7 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly coated on an aluminum film with a thickness of 15 μm and vacuum dried at a temperature of 135° C. to prepare a positive electrode for a lithium secondary battery.

[0175] For the above-mentioned positive electrode, lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separator, and a button cell was prepared using an electrolyte containing 1.15 M LiPF6 in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0176] Experimental Example 1: Determination of the full width at half maximum

[0177] The full width at half maximum of the second lithium composite oxide of the above-mentioned example was measured and is shown in Table 1 below.

[0178] Furthermore, the a-axis lattice constant and the c-axis lattice constant of the second lithium composite oxide of the above-mentioned example were measured and shown in Table 1 below.

[0179] The determination method is as described above.

[0180] Table 1

[0181]

[0182] Experimental Example 2: XRD determination

[0183] The X-ray diffraction analysis results of the first lithium composite oxide and the second lithium composite oxide of the above-mentioned example are shown in Figure 2 middle.

[0184] X-ray diffraction analysis was performed using Cu Kα radiation The measurement was performed using a Bruker D8 Advance diffractometer with a step size (° / step) of 0.02° / step and a measurement time of 0.1 s / step.

[0185] refer to Figure 2 It can be confirmed that the (104) displacement occurs as the cobalt content added during the first heat treatment increases, but the cobalt content added during the second heat treatment has no effect on the position change of the (104) displacement.

[0186] Furthermore, it was confirmed that the doping effect in the finally prepared positive electrode active material was maintained according to the cobalt content added during the first heat treatment.

[0187] Experimental Example 3: Determination of residual lithium

[0188] The measurement results of residual lithium in the first lithium composite oxide and the second lithium composite oxide of the above-mentioned example are shown in Table 2 below.

[0189] The residual lithium was determined by pH titration until the amount of 0.1M HCl used when the pH reached 4. First, 5 g of the oxide was added to 100 ml of deionized water (DIW) and stirred for 15 minutes before filtering. Then, 50 ml of the filtered solution was taken and 0.1M HCl was added thereto to determine the HCl consumption caused by the pH change, determine Q1 and Q2, and calculate the residual LiOH and Li2CO3 by the following calculation formula.

[0190] M1 = 23.94 (LiOH molecular weight)

[0191] M2 = 73.89 (Li2CO3 molecular weight)

[0192] LiOH(ppm)=

[0193]

[0194] Li2CO3(ppm)=

[0195]

[0196] Table 2

[0197]

[0198] Referring to Table 2 above, it can be confirmed that the residual lithium in the positive electrode active material decreases as the cobalt content added during the first heat treatment and the second heat treatment increases, but even if the total cobalt content added is the same, the cobalt content added during the second heat treatment has a greater impact on the reduction of residual lithium.

[0199] Furthermore, it was confirmed that the residual lithium removal effect in the finally prepared positive electrode active material was achieved without the need for a washing process, and in particular, it was confirmed that the residual lithium removal effect was enhanced by the cobalt added during the second heat treatment.

[0200] Furthermore, it can be confirmed that Examples 1, 2, and 3 in which the Co content was increased during the second heat treatment showed the lowest residual lithium level.

[0201] Experimental Example 4: Evaluation of electrochemical characteristics

[0202] The results of electrochemical characteristic evaluation of the lithium secondary batteries of the above examples are shown in Table 3 below.

[0203] Initial charge / discharge capacity determination The initial charge capacity and initial discharge capacity were determined by charge / discharge experiments using an electrochemical analyzer (Toyo, Toscat-3100) at a temperature of 25°C and a voltage range of 2.0V to 4.25V with a discharge rate of 0.1C to calculate the initial reversible efficiency.

[0204] The charge-discharge rate (C-rate) was measured by using an electrochemical analyzer (Toyo, Toscat-3100) to perform a charge-discharge experiment with a discharge rate of 0.1C to 10.0C under the conditions of a temperature of 25°C and a voltage range of 2.5V to 4.25V to measure the output efficiency (charge-discharge rate (C-rate)) of 10.0C / 0.1C.

[0205] The high temperature life measurement was performed at 25°C, 2.0V to 4.25V, with a charge and discharge rate of 0.1C / 0.1C once, at a voltage range of 2.5V to 4.25V, with a charge and discharge rate of 0.2C / 0.2C once, and at 45°C, 2.5V to 4.25V, with a charge and discharge rate of 50 times at a voltage range of 1.0C / 5.0C. The ratio of the discharge capacity at the 50th cycle to the initial capacity was then measured (capacity retention).

[0206] Table 3

[0207]

[0208] According to Table 3, it can be confirmed that the initial charge and discharge capacities of Examples 1, 5, and 8 in which the second heat treatment temperature is 705° C. are the highest.

[0209] Furthermore, it was confirmed that the high temperature life characteristics of Examples 1, 2, and 3 in which the Co content ratio during the first heat treatment and the second heat treatment was 1 / 3 were good.

[0210] On the other hand, it was confirmed that Example 1, in which the Co content ratio during the first heat treatment and the second heat treatment was 1 / 3 and the second heat treatment temperature was 705° C., achieved the best battery characteristics.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material comprises a lithium composite oxide. According to the results of X-ray diffraction analysis using CuKα rays, the following relationship 1 is satisfied in the XRD pattern obtained by Rietveld fitting: Relationship 1: 0.110 ≤ FWHM (104) ≤0.170, In the above equation 1, the above FWHM (104) It refers to the full width at half maximum of the (104) crystal plane at the XRD peak defined by the hexagonal lattice with the R-3m space group.

2. The positive electrode active material according to claim 1, characterized in that According to the results of X-ray diffraction analysis using CuKα rays, the following relationship 2 is satisfied in the XRD pattern obtained by Rietveld fitting: Relationship 2: 0.080 ≤ FWHM (003) ≤0.130, In the above equation 2, the above FWHM (003) It refers to the full width at half maximum of the (003) crystal plane at the XRD peak defined by the hexagonal lattice with the R-3m space group.

3. The positive electrode active material according to claim 1, characterized in that The a-axis lattice constant is 2.860 to 2.

890.

4. The positive electrode active material according to claim 1, characterized in that The c-axis lattice constant is 14.190 to 14.

200.

5. The positive electrode active material according to claim 1, characterized in that The positive electrode active material is in a bimodal form including first positive electrode active material particles having an average particle size D50 of 8 μm or more and second positive electrode active material particles having an average particle size D50 of 7 μm or less.

6. A method for preparing a positive electrode active material, characterized in that: The steps include: preparing an oxide precursor; and The first lithium composite oxide is prepared by performing a first heat treatment on a first mixture including the prepared oxide precursor, the lithium-containing compound and the first cobalt-containing compound.

7. The method for preparing a positive electrode active material according to claim 6, characterized in that: After the step of preparing the first lithium composite oxide, the method further includes the step of preparing a second lithium composite oxide by performing a second heat treatment on a second mixture including the first lithium composite oxide and a second cobalt-containing compound.

8. The method for preparing a positive electrode active material according to claim 7, characterized in that: When in the step of preparing the above-mentioned first lithium composite oxide, the molar percentage of cobalt contained in the above-mentioned first cobalt-containing compound relative to the total amount of metal in the prepared above-mentioned oxide precursor is set to A, and in the step of preparing the above-mentioned second lithium composite oxide, the molar percentage of cobalt contained in the above-mentioned second cobalt-containing compound relative to the total amount of metal other than lithium in the prepared above-mentioned first lithium composite oxide is set to B, 0.1≤A / B≤0.

5.

9. The method for preparing a positive electrode active material according to claim 6, characterized in that: The first cobalt-containing compound is Co3O4.

10. The method for preparing a positive electrode active material according to claim 7, characterized in that: The second cobalt-containing compound is Co3O4.

11. The method for preparing a positive electrode active material according to claim 7, characterized in that: The second heat treatment temperature Y is 690°C <Y<720℃。 12. A positive electrode active material, characterized in that: Prepared by the preparation method according to claim 6.

13. A positive electrode, characterized in that: The positive electrode active material according to any one of claims 1 to 12 is included.

14. A secondary battery, characterized in that: The positive electrode active material according to any one of claims 1 to 12 is included.